Analysis of morphological, structural and electrical properties of annealed TiO2 nanowires deposited by GLAD technique. (June 2017) - Shougaijam, B.; Swain, R.; Ngangbam, C.; Lenka, T. R.
Abstract: The effect of annealing on vertically aligned TiO2 NWs deposited by glancing angle deposition (GLAD) method on Si substrate using pressed and sintered TiO2 pellets as source material is studied. The FE-SEM images reveal the retention of vertically aligned NWs on Si substrate after annealing process. The EDS analysis of TiO2 NWs sample annealed at 600 °C in air for 1 h shows the higher weight percentage ratio of ∼2.6 (i.e., 72.27% oxygen and 27.73% titanium). The XRD pattern reveals that the polycrystalline nature of anatase TiO2 dominates the annealed NWs sample. The electrical characteristics of Al/TiO2 -NWs/TiO2 -TF/p-Si (NW device) and Al/TiO2 -TF/p-Si (TF device) based on annealed samples are compared. It is riveting to observe a lower leakage current of ∼1.32 × 10 −7 A/cm 2 at +1 V with interface trap density of ∼6.71 × 10 11 eV −1 cm −2 in NW device compared to ∼2.23 × 10 −7 A/cm 2 in TF device. The dominant leakage mechanism is investigated to be generally Schottky emission; however Poole-Frenkel emission also takes place during high reverse bias beyond 4 V for NWs and 3 V for TF device.